SYNTHESIS OF N-ARILIDENHYDRAZIDE OF CARBOXYETHYLALGINIC ACID - T. I. Taradeyko; S. N. Galasheva; D. N. Kutkina; O. B. Schennikova; A. A. Iozep (Разработка и регистрация лекарственных средств, 2019)
The reaction of hydrazide of corboxyethyl alginic acid with aromatic aldehydes was studied. The effect of the time limit, the reagent ratio and the structure of the carbonyl compound to delivery end of the product were determined. It has been established that electron-withdrawing substituting groups in the benzene ring of aldehyde accelerate the reaction of formation of hydrazones, and electron-donating-inhibit.